Validation of the French Smoking Cessation Motivation Scale with French Smokers Using a Mobile App for Smoking Cessation - Luz Adriana Bustamante; Lucia Romo (MDPI AG, 2022)
To tailor and predict the outcomes of smoking cessation treatment, it is essential to identify the nature of motivation, as it is the basis for long-term change in healthy behaviors according to self-determination theory (SDT). The purpose of this study is to examine the psychometric properties of the French Smoking Cessation Motivation Scale (F-SCMS). The factorial structure and the psychometric properties were assessed with French-speaking users who had started a 9-step preparation program through a mobile app for smoking cessation (n = 13,044). The results of the present study confirmed content validity (CFI = 0.905, SRMR = 0.045, RMSEA = 0.087) and good internal consistency (α = 0.86, ωh = 0.7, ωt = 0.89) with CFA. The convergent validity was very small, but there were highly significant positive correlations between the willingness and readiness to quit with integrated and intrinsic subscales (rs = 0.25-0.37, p < 0.001). The amotivation subscale significantly had no correlation with any degree of willingness (r = 0.01, p < 0.001), ability (r = 0.01, p < 0.001), and readiness to quit (r = 0.02, p < 0.001). This scale facilitates future research regarding the nature of motivation to quit smoking in the French-speaking population.